Identification of a Guanine-Rich-Oligonucleotides (GRO) in the Promoter of the MYCN Gene which Inhibits Neuroblastoma Growth - Islam, Md Ashraful; Sheikh, Fadlan A; Thomas, Shelia D; Magrabi, Tarek; Alrashid, Tariq; Miller, Donald M (International Journal of Innovative Research in Medical Science, 2022)
Neuroblastoma is the most common solid tumor of childhood malignancy. The biological properties vary from indolent to aggressive depending on how different genes play their role in transforming neural crest cells leading to spontaneous regression to an unfavorable outcome. Guanine-Rich Oligonucleotides (GRO) are being tested as a potential target for an anti-cancer drug. In this study, we have identified GROs at the promoter regions of the MYCN oncogene (MYCN-15) and it formed quadruplex in-vitro shown by circular dichroism (CD). Then three neuroblastoma cell lines were used to explore the effect of MYCN-15 on different biological properties: cellular growth, differentiation, and death. The neuroblastoma cell lines SH-SY5Y and SK-N-AS have a single copy of the MYCN gene, whereas the SK-N-BE2 cell line has multiple copies (n-Myc amplified). MYCN-15-induced cellular differentiation in both SK-N-AS and SH-SY5Y cells was followed by cell death in the SH-SY5Y cell line only. MTT [3-(4,5-dimethylthiazol-2-Yl)-2,5-diphenyltetrazolium bromide] assay revealed, that there was modest growth inhibition in both SH-SY5Y (~58%) and SK-N-BE2 (~38%) cells when treated with MYCN-15 oligonucleotide. There were no significant changes in survivin protein expression in both SK-N-AS and SH-SY5Y cells when treated with MYCN-15 oligonucleotides. Taken together, MYCN-15 can be used as an essential target oligonucleotide for treating human neuroblastoma.